2014
DOI: 10.1007/s10029-014-1232-x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired abdominal intercostal hernia: case report and systematic review of the literature

Abstract: AAIH should be always suspected when chest swelling occurs after a minor or major trauma, and CT must be promptly performed to rule out diaphragmatic or abdominal viscera injury. This condition requires surgery to prevent serious complications, the first-choice technique should be mesh tension-free repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 27 publications
0
45
0
5
Order By: Relevance
“…Less than 40 cases of transdiaphragmatic intercostal hernias have been reported in the literature [1,2]. Even fewer still are cases of intercostal hernias under an intact diaphragm [3]. Intercostal hernias are associated with an increase in abdominal pressure and may develop acutely or over a number of years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Less than 40 cases of transdiaphragmatic intercostal hernias have been reported in the literature [1,2]. Even fewer still are cases of intercostal hernias under an intact diaphragm [3]. Intercostal hernias are associated with an increase in abdominal pressure and may develop acutely or over a number of years.…”
Section: Discussionmentioning
confidence: 99%
“…Positive intrathoracic pressure forces the contents out through weakened areas of the chest wall. The majority of cases share the predisposing characteristics of obesity: COPD, advanced age, smokers, and connective tissue disorders [3]. The majority of intercostal hernias are the result of a traumatic mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intercostal hernia of chest wall is more common than abdominal intercostal hernia. Recently intercostal hernias have been divided into two types: with or without diaphragmatic defect (4) . Abunnaja et al (2) reported a case of acquired abdominal intercostal hernia in a 51 years old female patient with past history of stab injury locally.…”
Section: Introductionmentioning
confidence: 99%